2021
DOI: 10.1055/a-1494-3892
|View full text |Cite
|
Sign up to set email alerts
|

Normierung der deutschen Fassung der Highly Sensitive Person Scale (HSPS-G) – Selbstbeurteilungsskala an einer deutschsprachigen Stichprobe

Abstract: Zusammenfassung Problem Die deutsche Fassung der Highly Sensitive Person Scale (HSPS-G) ist ein Verfahren zur Feststellung der Ausprägung des Merkmals Feinfühligkeit. Diese Skala wurde bisher in der deutschen Fassung validiert (Konrad & Herzberg, 2017), eine Normierung für die deutschsprachige Allgemeinbevölkerung steht allerdings noch aus. Methode Zur Erstellung von Normwerten der Skala für die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…On the one hand, studies disagree on the extent to which gender plays a role in the emergence of MPA (Dempsey & Comeau, 2019;Kenny, Driscoll, & Ackermann, 2014;Papageorgi, 2022;Robson & Kenny, 2017;Ryan 2004). On the other hand, research suggests that females are supposed to display higher traits of SPS (Herzberg et al, 2021). Considering an overrepresentation of the female gender in this sample and gender-related differences in the sensitivity trait, one needs to be cautious when generalizing these findings.…”
Section: Limitationsmentioning
confidence: 88%
See 3 more Smart Citations
“…On the one hand, studies disagree on the extent to which gender plays a role in the emergence of MPA (Dempsey & Comeau, 2019;Kenny, Driscoll, & Ackermann, 2014;Papageorgi, 2022;Robson & Kenny, 2017;Ryan 2004). On the other hand, research suggests that females are supposed to display higher traits of SPS (Herzberg et al, 2021). Considering an overrepresentation of the female gender in this sample and gender-related differences in the sensitivity trait, one needs to be cautious when generalizing these findings.…”
Section: Limitationsmentioning
confidence: 88%
“…While some people are more sensitive than others, SPS is thought to be a temperamental trait, manifested in our genes and associated with greater brain activity related to, for example, attention, awareness, self-other processing, and empathy (Acevedo, 2020;Acevedo et al, 2014). In a recent study, it was shown that females tend to be more sensitive than men and that sensitivity seemed to increase with age (Herzberg et al, 2021). Although SPS tends to affect only 20% to 31% of the population (Konrad, 2020;Lionetti et al, 2018), Aron (1997) stated that highly sensitive people often choose creative professions, such as writing, philosophy, or art.…”
Section: The Role Of Parenting Stylementioning
confidence: 99%
See 2 more Smart Citations